Combined arthroscopic and radioscopic management of tibial plateau fractures: report of 18 clinical cases - Pogliacomi, F.; Verdano, M.A.; Frattini, et al., M. (Acta Biomedica Atenei Parmensis, 2005)
Tibial plateau fractures are complex lesions capable of causing severe consequences if not appropriately treated. They are often the result of a high-energy trauma and, not rarely, are associated with significant soft-tissue and intra-articular injuries. Different therapeutic options can be managed in the treatment of these lesions. Minimally invasive surgery offers several advantages compared to other surgical techniques and allows, with less additional soft tissue damages, good reduction and stable fixation of the fracture. In this study we assessed the results of the combined arthroscopic and radioscopic assisted reduction and internal fixation of tibial plateau fractures in 18 patients affected by Schatzker type I, II, III, IV fractures. According to Hohl’s and Rasmussen’s grading system, 16 out of 18 patients scored a satisfactory result.We experienced no complications due to arthroscopy.